Peningkatan Hasil Belajar Menulis Teks Deskriptif Sederhana melalui Model Pembelajaran Kooperatif STAD - Sri Lahir (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research aims to improve Learning Achievement in Writing Simple Descriptive Texts Through the STAD Cooperative Learning Model for Class IXB Negeri 6 Sukoharjo Students in Semester 1 of the 2022/2023 Academic Year" The research method uses Classroom Action Research which is carried out in two cycles, each cycle consists of two meetings, with four stages of research: planning, implementation, observation and reflection. The subjects of this study are students of Class IXB Negeri 6 Sukoharjo in Semester 1 of the 202/2023 Academic Year with a total of 36 students. The data collection techniques used are observation, interviews, tests, and documentation. The data analysis used in this study is a qualitative descriptive analysis. The result of this study is to improve Learning Achievement in Writing Simple Descriptive Texts Through the STAD Cooperative Learning model. The results of the success in this study are evidenced by the increase in student learning outcomes in the first cycle of students who managed to get KKM scores, an increase from the initial condition of 18 students (50%) to 23 students (64%) or there was an increase of 14% compared to the initial condition. Meanwhile, in the second cycle, it increased to 32 students (88.8%) or there was an increase of 24.8% from before. Based on the results of this study, it can be concluded that the application of the STAD Learning Model can improve the learning outcomes of Writing Simple Descriptive Texts in Class IXB Negeri 6 Sukoharjo students in Semester 1 of the 2022/2023 Academic Year.